Flux paste for improving Mini LED welding quality and preparation method thereof
By using solder paste composed of liquid resin, surfactant and multifunctional additives, the existing Mini LED solder paste has solved the problems of poor wetting and weak stability, achieving high wetting, low hollow rate and high collapse resistance, and improving the welding quality of Mini LED.
Patent Information
- Application Number
- CN202510105197.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The existing Mini LED welding paste has defects such as poor wetting, easy to form solder joint holes, weak stability, and weak collapse resistance, which affects the welding quality.
The solder paste consisting of liquid resin, surfactant and multifunctional additives, specifically includes an epoxy resin, a polyurethane resin, a blend of polyvinyl pyrrolidone and a liquid polymer alcohol compound, and a carboxylated PAMAM or a mixture thereof with dendritic PAMAM.
It improves the wettability of the solder paste, reduces the void rate of the solder joint, enhances stability and anti-collapse performance, thereby improving the welding quality of Mini LEDs.
Smart Images

Figure BDA0005255240650000081 
Figure BDA0005255240650000091 
Figure BDA0005255240650000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solder technology, and in particular relates to a soldering paste for improving Mini LED soldering quality and a preparation method thereof. Background Art
[0002] Mini LED is a "sub-millimeter light-emitting diode" that uses LED chips between 50μm and 200μm, combined with a drive circuit, to form a pixel unit with a pitch of 0.3mm to 1.5mm. Due to the small size of Mini LED, there are a large number of chips and solder joints on each circuit board, so the welding quality directly affects the performance and reliability of the product.
[0003] Solder paste is an important material in the LED welding process. It is a paste-like substance composed of alloy powder solder and flux paste. Among them, flux paste is a good carrier of solder, which is used to adjust the viscosity of solder paste to improve the comprehensive performance of solder paste such as storage and printing. The main functions of flux paste are: to remove oxides on the surface of the metal to be welded and prevent the re-oxidation of solder and welding surface; to reduce the surface tension of solder, promote mutual wetting between solder and welded metal, and ensure the formation of a stable insulating layer after welding. It can be seen that the quality of flux paste, as an important material in the welding process, has a crucial impact on the welding effect.
[0004] At present, the most common Mini LED solder paste is rosin-based solder paste, which has defects such as excessive residue and solder beads. In order to solve this problem, some solder pastes use epoxy resin and organic acid composite materials instead of rosin and organic solvents to form solvent-free and rosin-free resin solder pastes. However, there are defects such as poor wettability, easy formation of solder joint voids, weak stability, and weak anti-collapse performance. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a flux paste and a preparation method thereof for improving the welding quality of Mini LED, aiming to solve at least one technical problem in the background technology.
[0006] The present invention is achieved in that:
[0007] A first aspect of the present invention provides a solder paste for improving the soldering quality of Mini LEDs, wherein the solder paste comprises a liquid resin, a surfactant and a multifunctional additive;
[0008] According to the weight ratio, liquid resin: surfactant: multifunctional additive = 1: 0.1 ~ 0.5: 0.1 ~ 0.5;
[0009] The liquid resin includes epoxy resin and polyurethane resin; according to the weight ratio, epoxy resin: polyurethane resin = 5 to 20:1;
[0010] The surfactant is a blend of polyvinyl pyrrolidone and a liquid polymer alcohol compound;
[0011] The multifunctional auxiliary agent is carboxylated PAMAM or a mixture of carboxylated PAMAM and dendritic PAMAM.
[0012] Preferably, the soldering paste further comprises a thixotropic agent, and the thixotropic agent is selected from at least one of hydrogenated castor oil, polyamide wax, and fumed silica.
[0013] Preferably, the amount of the thixotropic agent is 0.5wt% to 10wt% of the liquid resin.
[0014] Preferably, the liquid polymer alcohol compound is at least one selected from polyethylene glycol, methoxypolyethylene glycol, polypropylene glycol, and polyvinyl alcohol.
[0015] Preferably, in the surfactant, the weight ratio of polyvinyl pyrrolidone to the liquid polymer alcohol compound is 1:2 to 2:1.
[0016] Preferably, the generation number of the carboxylated PAMAM or dendritic PAMAM is 1 to 5 generations.
[0017] Preferably, in the mixture of the carboxylated PAMAM and the dendritic PAMAM, the weight ratio of carboxylated PAMAM:dendritic PAMAM is 1 to 5:1.
[0018] A first aspect of the present invention provides a method for preparing the above-mentioned solder paste for improving the welding quality of Mini LEDs, which comprises the following steps:
[0019] Mix epoxy resin, polyurethane resin and part of surfactant in proportion, heat to 50℃~70℃ and stir evenly;
[0020] Add the multifunctional additive and the remaining surfactant simultaneously or step by step, and stir evenly at 80℃~120℃;
[0021] Stop heating and continue stirring until the temperature drops to 50°C to 70°C. Stop stirring and cool to room temperature.
[0022] Preferably, the preparation method comprises the following steps:
[0023] Mix epoxy resin, polyurethane resin and part of surfactant in proportion, heat to 50℃~70℃ and stir evenly;
[0024] Add thixotropic agent and stir until there are no particles or stratification;
[0025] Add the multifunctional additive and the remaining surfactant simultaneously or step by step, heat to 80℃~120℃, and stir evenly;
[0026] Stop heating and continue stirring until the temperature drops to 50°C to 70°C. Stop stirring and cool to room temperature.
[0027] Preferably, the part of the surfactant refers to the amount used in this step which is 30 wt% to 50 wt% of the total amount of the surfactant.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention uses epoxy resin and polyurethane resin instead of rosin, polyvinyl pyrrolidone and liquid high molecular alcohol compounds to form a surfactant, and carboxylated PAMAM or a mixture of carboxylated PAMAM and dendritic PAMAM to form a multifunctional additive to prepare a solder paste with high wettability, low solder joint void rate, high stability and strong anti-collapse performance.
[0030] 2. The present invention uses epoxy resin and polyurethane resin as composite liquid resin, which has the advantages of high adhesion, resistance to glue cracking, strong weather resistance, etc.
[0031] 3. The multifunctional auxiliary agent of the present invention has the functions of a resin activator and a curing agent, and can also improve the heat resistance of the solder paste and prevent oxidation.
[0032] 4. The present invention blends polyvinyl pyrrolidone with liquid polymer alcohol compounds to play the functions of surface activity, lubrication, solubilization, dispersion, etc., and also enhances the antioxidant stability, avoiding the decomposition of bubbles when reacting with air at high temperature during welding, thereby inhibiting the generation of solder joint voids. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] A method for preparing a soldering paste for improving the soldering quality of Mini LEDs, comprising steps S1 to S5.
[0035] S1. Weigh the raw materials
[0036] The raw materials of solder paste include liquid resin, surfactant and multifunctional additives;
[0037] In the present invention, liquid resin is used to replace the rosin in conventional solder paste, and the liquid resin includes epoxy resin and polyurethane resin; epoxy resin is a high molecular polymer, which refers to a general term for a class of polymers containing two or more epoxy groups in the molecule, and is a condensation product of epichlorohydrin and bisphenol A or polyol. Due to the chemical activity of the epoxy group, a variety of compounds containing active hydrogen can be used to open the ring, solidify and cross-link to form a network structure, which is a thermosetting resin; and epoxy resin has high adhesion, which is very suitable for the packaging process of Mini LED, ensuring the chip size accuracy during the welding process and improving the yield of chip packaging; in the specific implementation, the epoxy resin adopts any liquid epoxy resin allowed in the art, and the following embodiment is illustrated by bisphenol A type epoxy resin (E-40 type), but it is not limited to this epoxy resin, and other liquid epoxy resins not listed are also applicable. Although epoxy resin has high adhesion, it has poor weather resistance and large shrinkage, which makes the surface of the final solder paste easily deformed, brittle or even cracked, and thus has poor stability; in order to solve this technical problem, the present invention adds a small amount of liquid polyurethane resin to the epoxy resin to form a composite liquid resin. In a specific implementation, according to the weight ratio, epoxy resin: polyurethane resin = 5 to 20:1, for example, it can be 5:1, 10:1, 15:1, 20:1; but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. Within this range, the liquid resin has the advantages of high adhesion, anti-crack, strong weather resistance, etc.
[0038] Since the solder paste should have two main functions of removing oxides and reducing the surface tension of the solder paste, a surfactant and a multifunctional additive are added in the present invention. In a specific implementation, according to the weight ratio, liquid resin: surfactant: multifunctional additive = 1:0.1~0.5:0.1~0.5.
[0039] The surfactant is a blend of polyvinyl pyrrolidone and liquid polymer alcohol compounds. The main function of polyvinyl pyrrolidone is a surfactant, which has excellent dispersibility and film-forming properties. Based on its dispersibility, it plays a steric hindrance role on the resin, thereby playing the role of a surfactant; the liquid polymer alcohol compound is selected from at least one of polyethylene glycol, methoxy polyethylene glycol, polypropylene glycol, and polyvinyl alcohol, and has the functions of a surfactant, a lubricant, a cosolvent, a stabilizer, a dispersant, etc.; wherein the molecular weight of polyethylene glycol is selected from 1400 to 3500, the molecular weight of methoxy polyethylene glycol is selected from 1000 to 2000; the molecular weight of polypropylene glycol is selected from 500 to 1000; polyvinyl alcohol uses polyvinyl alcohol with a low degree of polymerization, and the molecular weight is generally 25,000 to 35,000, preferably 35,000; in a specific implementation, the weight ratio of polyvinyl pyrrolidone to the polymer alcohol compound is 1:2 to 2:1; the polyvinyl pyrrolidone powder can be formed into a uniformly dispersed blend with the liquid polymer alcohol compound under mechanical stirring or ultrasonic dispersion. In addition, the blending of polyvinyl pyrrolidone with liquid polymer alcohol compounds can enhance the antioxidant stability of the polymer alcohol compounds to a certain extent, avoiding the decomposition of the polymer alcohol compounds by reacting with air at high temperatures during welding to produce bubbles, thereby inhibiting the voids in the solder joints.
[0040] The multifunctional additive is carboxylated PAMAM or a mixture of carboxylated PAMAM and dendritic PAMAM. The multifunctional additive has the functions of a resin activator and a resin curing agent, and can also improve the heat resistance of the solder paste and prevent oxidation.
[0041] Carboxylated PAMAM (PAMAM-COOH) means that the amino groups at the ends of the PAMAM molecules are partially or completely replaced by carboxyl groups, thereby introducing more hydrophilic groups. PAMAM is a polyamide-amine dendrimer, a polymer compound with a three-dimensional structure. Its branched structure provides a large number of active groups that can carry various functional molecules. The molecular structure of PAMAM contains a large number of tertiary amines, which can promote the cross-linking reaction between the hydroxyl groups inside the resin and its epoxy groups at high temperatures, as well as the reaction between the PAMAM amino groups and epoxy molecules to form a greater cross-linking density, thereby improving the stability, mechanical properties and heat resistance of the solder paste. In specific implementation, PAMAM-COOH is a hydrolysis and condensation reaction between PAMAM and aldehyde acid, and the amino groups in PAMAM are converted into carboxyl groups, thereby introducing carboxyl groups.
[0042] PAMAM-COOH can further improve the lubricity of solder paste, and good wettability helps solder paste to better cover and adhere to the substrate, thereby improving welding quality; PAMAM-COOH makes the residue after welding easier to be washed off with water, which helps to remove the residue of solder paste, thereby improving cleanliness; in addition, carboxyl groups can react with oxides to a certain extent, for example, carboxyl groups and metal ions can remove the oxide film of pads and solder paste in the form of metal soaps; in the mixture of carboxylated PAMAM and dendritic PAMAM, the content of carboxylated PAMAM is not less than that of dendritic PAMAM, preferably, in terms of weight ratio, carboxylated PAMAM: dendritic PAMAM=1-5:1; the generation of carboxylated PAMAM or dendritic PAMAM is 1-5 generations, because: low-generation PAMAM is in liquid form, and it is more evenly mixed with resin liquid-liquid; high-generation PAMAM usually has a higher surface charge density and a larger hydrophobic cavity, and is prone to residues that are difficult to clean after welding.
[0043] In a specific implementation, the solder paste further includes a thixotropic agent, and the thixotropic agent can be any thixotropic agent permitted in the art, such as at least one of hydrogenated castor oil, polyamide wax, and fumed silica; the amount of the thixotropic agent is 0.5wt% to 10wt% of the liquid resin. The following embodiment uses 5wt% of fumed silica (based on the liquid resin) as an example, but is not limited to the listed thixotropic agents, and other thixotropic agents not listed are also applicable.
[0044] S2, high temperature emulsified resin
[0045] Epoxy resin, polyurethane resin and part of surfactant are mixed in proportion and added into an emulsifier, heated to 50°C to 70°C, and stirred at high speed until uniform; the amount of surfactant used is 30wt% to 50wt% of the total amount.
[0046] S3. Add thixotropic agent and stir until there are no particles or stratification.
[0047] S4. Add the multifunctional additive and the remaining surfactant simultaneously or step by step, heat and raise the temperature, and stir evenly at 80°C to 120°C;
[0048] Add the multifunctional additive and the remaining surfactant into the emulsifier at the same time, heat to 80℃~120℃, and stir evenly at high speed until all the raw materials are melted into liquid;
[0049] Alternatively, first add the remaining surfactant and heat to 80°C-120°C, and stir at high speed to make it uniform; keep warm and then add the multifunctional additive, and stir at high speed until all the raw materials are melted into liquid.
[0050] The temperature in this step is adjusted according to the type of surfactant. The following embodiments are illustrated with 100° C., but are not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0051] S5. Stop heating and continue stirring until the temperature drops to 50°C to 70°C. Stop stirring and then cool to room temperature to obtain solder paste.
[0052] In a specific implementation, a grinder may be used to grind and refine the solder paste to obtain a solder paste with a smaller particle size.
[0053] The invention adopts a method of first emulsifying by low temperature heating and then synthesizing by high temperature reaction to prepare the solder paste, which has small particle size and good fluidity.
[0054] Example 1
[0055] A method for preparing a solder paste for improving the welding quality of Mini LEDs comprises the following steps:
[0056] S1. Raw material preparation
[0057] ① Liquid resin: The total amount is 600g, including 500g epoxy resin and 100g polyurethane resin, the ratio of the two is 5:1;
[0058] ② Surfactant: The total amount is 60g, including 20g polyvinyl pyrrolidone and 40g polyethylene glycol 2000 (PEG-2000), the ratio of the two is 1:2;
[0059] ③Multifunctional additives: The total dosage is 60g, including 30g G1 PAMAM-COOH and 30g G1PAMAM;
[0060] S2, epoxy resin, polyurethane resin, and 50 wt% of surfactant are mixed in proportion and added into an emulsifier, heated to 50°C, and stirred at high speed until uniform;
[0061] S3. Add 30 g of fumed silica and stir until there are no particles or stratification.
[0062] S4. First add the remaining surfactant and heat to 100°C, then stir at high speed to make it evenly distributed; keep warm and then add the multifunctional additive, stirring at high speed until all the raw materials are melted into liquid.
[0063] S5. Stop heating and continue stirring until the temperature drops to 50° C. Stop stirring and then cool to room temperature to obtain solder paste.
[0064] The solder paste prepared in Example 1 was mixed with solder powder (Sn 96.5 Ag 3.0 Cu 0.5The alloy) was mixed into solder paste in a weight ratio of 12:88, and the performance of the solder paste was tested. The test method includes:
[0065] (1) Viscosity: Use a viscometer to test the viscosity of solder paste at room temperature;
[0066] (2) Spreading coefficient. A higher spreading coefficient means that the solder paste has better wettability and fluidity. A spreading experiment was conducted according to GB / T11364-2008 “Test method for wettability of solder”. The spreading coefficient K was calculated according to the following formula (1):
[0067]
[0068] H is the height of the solder paste after spreading on the surface of the base material, in millimeters; D is the diameter of a sphere with the same volume as the solder paste, in millimeters, D = 1.24V 1 / 3 , V is the ratio of the mass and density of the solder paste used in the test;
[0069] (3) Void rate: The solder paste was used to reflow solder the optical signal processor (OSP) circuit board using a reflow machine. The solder paste was printed on the circuit board using a special steel mesh and evaluated after soldering in a reflow oven. The void rate of some test solder balls was observed using X-Ray.
[0070] (4) Stability: the test method is as follows: 100g solder paste is placed in a high-speed centrifuge and centrifuged continuously for 30 minutes, and the state of the solder paste is observed at room temperature; if the solder paste is still fine and has strong fluidity after centrifugation, it is judged as Grade 1; if the solder paste has little roughness and good fluidity after centrifugation, it is judged as Grade 2; if the solder paste has high roughness and poor fluidity after centrifugation, it is judged as Grade 3; if the solder paste is sandy or even dry after centrifugation, it is judged as Grade 4;
[0071] (5) Collapse resistance. Collapse resistance can be expressed by the minimum bridge spacing of the solder paste during thermal collapse. The smaller the spacing, the better the collapse resistance. The test method is: refer to SJ / T11186-2019 "General Specification for Solder Paste". Due to the small size and fine spacing of MiniLED, collapse represents the ability of the solder paste to maintain the printed shape during printing. If the collapse performance is too poor, solder will be connected during the soldering process, resulting in a short circuit.
[0072] Example 2
[0073] In this embodiment, the ratio of epoxy resin to polyurethane resin is adjusted on the basis of Embodiment 1 (the total amount of liquid resin remains unchanged), and other conditions are the same as those in Embodiment 1. The performance of the solder paste composed of flux paste and solder prepared in this embodiment is tested by the same method as in Embodiment 1, and the results are shown in Table 1.
[0074] Table 1
[0075]
[0076] It can be seen from the data in Table 1 that in the liquid resin, as the content of epoxy resin increases, the viscosity first decreases, then increases, and then decreases, and the spreading coefficient first increases and then decreases; the reason is that the viscosity of epoxy resin and polyurethane resin is different, and changes with the change of the ratio of the two. In the subsequent high-temperature synthesis process, cross-linking occurs between epoxy resin and polyurethane resin, and between them and additives, which causes fluctuations in viscosity and spreading coefficient. When epoxy resin: polyurethane resin = 5:1~20:1, the overall viscosity is maintained above 150Pa·s, and the spreading coefficient is maintained above 84%; the void rate does not change significantly, and the stability can basically be maintained at level 2 or level 1; the spacing at the minimum bridge is not more than 0.05mm, indicating that its anti-collapse performance is relatively excellent, among which there is no bridge at 10~15:1, which can better meet the welding requirements of Mini LED under ultra-fine spacing conditions and improve welding quality. In view of this, epoxy resin: polyurethane resin = 5:1~20:1, preferably 10~15:1.
[0077] Example 3
[0078] In this embodiment, the composition of the surfactant and the type of the liquid polymer alcohol compound are adjusted on the basis of Embodiment 1. Other conditions are the same as those in Embodiment 1. The performance of the solder paste composed of the flux paste and the solder prepared in this embodiment is tested by the same method as that in Embodiment 1. The results are shown in Table 2.
[0079] Table 2
[0080]
[0081] It can be seen from the data in Table 2 that when a single polyvinyl pyrrolidone or liquid polymer alcohol compound is used as an active agent, the performance of the solder paste formed by mixing the flux paste with the tin alloy is greatly reduced; for the composite surfactant composed of polyvinyl pyrrolidone and methoxy polyethylene glycol, polyethylene glycol, polypropylene glycol, polyvinyl alcohol, etc., the spreading coefficient, void rate, stability, and bridge spacing of the solder paste all meet the requirements, indicating that the flux paste has excellent lubricity, activity, stability and collapse resistance, and has high welding quality. Among them, the performance of the flux paste prepared by methoxy polyethylene glycol as a liquid polymer alcohol compound and polyvinyl pyrrolidone is the best.
[0082] Example 4
[0083] In this embodiment, the ratio of polyvinyl pyrrolidone to liquid high molecular alcohol compound in the surfactant is adjusted on the basis of Example 1 (the total amount of the surfactant remains unchanged), and other conditions are the same as those in Example 1. The performance of the solder paste composed of flux paste and solder prepared in this embodiment is tested by the same method as in Example 1. The results are shown in Table 3.
[0084] Table 3
[0085]
[0086] It can be seen from the data in Table 3 that when the ratio of polyvinyl pyrrolidone to liquid polymer alcohol compound is between 2:1 and 1:2, the spreading coefficient, void ratio, stability and bridge spacing of the solder paste all meet the requirements. When the value exceeds this range, the performance of the solder paste is significantly reduced.
[0087] Example 5
[0088] In this embodiment, the total amount of surfactant is adjusted on the basis of Example 1 (the ratio of polyvinyl pyrrolidone to liquid polymer alcohol compound remains unchanged), and other conditions are the same as those in Example 1. The performance of the solder paste composed of flux paste and solder prepared in this embodiment is tested by the same method as in Example 1, and the results are shown in Table 4.
[0089] Table 4
[0090]
[0091] It can be seen from the data in Table 4 that when the total amount of surfactant increases, the viscosity decreases and the spreading coefficient increases. When the weight ratio of the total amount of surfactant to the liquid resin is 0.1 to 0.5:1, the voiding rate, stability and bridge spacing of the solder paste all meet the requirements. When the value exceeds this range, the performance of the solder paste is significantly reduced, especially the stability, voiding rate and anti-collapse properties are significantly deteriorated.
[0092] Example 6
[0093] In this embodiment, the composition and dosage ratio of the multifunctional auxiliary agent are adjusted on the basis of Example 1 (the total dosage of the multifunctional auxiliary agent remains unchanged), and other conditions are the same as those in Example 1. The performance of the solder paste composed of flux paste and solder prepared in this embodiment is tested by the same method as in Example 1, and the results are shown in Table 5.
[0094] Table 5
[0095]
[0096] It can be seen from the data in Table 5 that using carboxylated PAMAM or carboxylated PAMAM+PAMAM as a multifunctional additive effectively improves the spreading coefficient, reduces the void ratio, and improves the stability and collapse resistance. Preferably, carboxylated PAMAM (PAMAM-COOH): dendritic PAMAM = 1 to 5:1.
[0097] Example 7
[0098] In this embodiment, the multifunctional additive PAMAM generation is adjusted on the basis of Example 1 (the dosage and composition of the multifunctional additive remain unchanged), and other conditions are the same as those in Example 1. The performance of the solder paste composed of flux paste and solder prepared in this embodiment is tested by the same method as in Example 1, and the results are shown in Table 6.
[0099] Table 6
[0100] Group PAMAM Algebra Viscosity / Pa·s Spreading coefficient / % Void rate / % stability Bridge spacing / mm Example 7-1 G2 155 85.7 4.9 1 No bridge Example 1 G1 161 85.1 5.4 2 0.06 Example 7-2 G3 150 87.3 4.6 1 No bridge Example 7-3 G4 147 88.0 4.1 1 No bridge Example 7-4 G5 142 87.9 4.4 1 0.06 Example 7-5 G6 135 80.7 8.3 4 0.25
[0101] It can be seen from the data in Table 6 that among the multifunctional additives, with the increase of carboxylated PAMAM and PAMAM generations, the spreading coefficient increases, the void ratio decreases, and the stability and anti-collapse properties improve. However, when the generation exceeds 5, the performance decreases significantly.
[0102] Example 8
[0103] In this embodiment, the total amount of the multifunctional additive is adjusted on the basis of Example 1 (the ratio of PAMAM-COOH to PAMAM remains unchanged), and other conditions are the same as those in Example 1. The performance of the solder paste composed of flux paste and solder prepared in this embodiment is tested by the same method as in Example 1, and the results are shown in Table 7.
[0104] Table 7
[0105]
[0106] From the data in Table 7, it can be seen that as the total amount of multifunctional additive increases, the spreading coefficient increases, the void rate decreases, and the stability and anti-collapse properties are improved. However, when it exceeds a certain value, the performance is greatly reduced. The reason is that excessive dosage leads to excessive dilution of the resin, a significant decrease in viscosity, reduced activity, and thus weakened welding performance. In view of this, the amount of multifunctional additive is 60g to 300g, that is, the weight ratio of the multifunctional additive to the liquid resin = 0.1 to 0.5:1, preferably 0.2 to 0.4:1.
[0107] Example 9
[0108] In this embodiment, the amount of surfactant used in steps S2 and S4 is the same as in embodiment 1, and other conditions are the same as in embodiment 1. The performance of the solder paste composed of flux paste and solder prepared in this embodiment is tested by the same method as in embodiment 1. The results are shown in Table 8.
[0109] Table 8
[0110]
[0111]
[0112] From the data in Table 8, we can see that adding different proportions of surfactants in the first emulsification step and the subsequent high-temperature synthesis respectively can increase the spreading coefficient, reduce the void ratio, and improve the stability and anti-collapse property. The reason is that in the S2 process, the resin emulsification efficiency is improved, and the activation efficiency is improved in the S4 process; and the amount of the first emulsification surfactant used is preferably 30% to 50% of the total amount. Within this range, the void ratio is low, the stability is good, and the anti-collapse property is strong.
[0113] Example 10
[0114] The heating temperature in step S2 of this embodiment is the same as that of embodiment 1, and other conditions are the same as those of embodiment 1. The performance of the solder paste composed of flux paste and solder prepared in this embodiment is tested by the same method as that of embodiment 1. The results are shown in Table 9.
[0115] Table 9
[0116]
[0117] It can be seen from the data in Table 9 that as the temperature in step S2 increases, the spreading coefficient increases, the void ratio decreases, and the stability and anti-collapse properties improve. However, the performance decreases after exceeding a certain temperature. The reason is that the high temperature causes the resin to solidify prematurely and does not react fully with subsequent additives.
[0118] Embodiment 11
[0119] The heating temperature in step S4 of this embodiment is the same as that of embodiment 1, and other conditions are the same as those of embodiment 1. The performance of the solder paste composed of flux paste and solder prepared in this embodiment is tested by the same method as that of embodiment 1. The results are shown in Table 10.
[0120] Table 10
[0121]
[0122] It can be seen from the data in Table 10 that as the temperature in step S4 increases, the spreading coefficient increases, the void rate decreases, and the stability and collapse resistance improve. The reason is that as the temperature increases, the additive reacts more fully with the resin and the activity of the flux increases. However, the performance decreases after exceeding a certain temperature because the network structure formed by the resin and the additive is destroyed due to excessively high temperature, resulting in poor performance.
[0123] Example 12
[0124] In this embodiment, the temperature at the end of stirring in step S5 is the same as in embodiment 1, and other conditions are the same as in embodiment 1. The performance of the solder paste composed of flux paste and solder prepared in this embodiment is tested by the same method as in embodiment 1. The results are shown in Table 11.
[0125] Table 11
[0126]
[0127] It can be seen from the data in Table 11 that as the temperature in step S5 increases, the spreading coefficient increases, the void ratio decreases, and the stability and anti-collapse properties improve. However, the performance decreases after exceeding a certain temperature. The reason is that the excessively high temperature causes the resin and additives to over-react, thereby causing the performance to deteriorate.
[0128] Example 13
[0129] The difference between this embodiment and embodiment 1 is only in step S5, and the other conditions are the same as those in embodiment 1. Specifically, step S5 of this embodiment is: adding the remaining surfactant and the multifunctional additive simultaneously, and stirring at high speed until all the raw materials are melted into liquid. The performance of the solder paste composed of the flux paste and the solder prepared in this embodiment is tested by the same method as in embodiment 1, and the results are shown in Table 12.
[0130] Table 12
[0131]
[0132] It can be seen from the data in Table 12 that both stepwise and simultaneous addition of the remaining surfactant and multifunctional additive in step S5 can enhance the performance of the solder paste, and the stepwise effect is better than the simultaneous addition.
[0133] Comparative Example 1
[0134] This comparative example adopts a conventional high temperature synthesis method to prepare solder paste, and the specific steps are as follows:
[0135] S1, same as S1 in Example 1;
[0136] S2, epoxy resin, polyurethane resin, surfactant, thixotropic agent and multifunctional additive are mixed in proportion and added into an emulsifier, heated to 150°C, and stirred at high speed until all raw materials are melted into liquid; turn off the heating, cool down to 100°C while stirring, stop stirring and cool to room temperature to obtain solder paste.
[0137] Comparative Example 2
[0138] This comparative example adopts a conventional high-temperature emulsification method to prepare solder paste, and the specific steps are as follows:
[0139] S1, same as S1 in Example 1;
[0140] S2, epoxy resin, polyurethane resin, and surfactant are mixed in proportion and added into an emulsifier, heated to 70°C, and stirred at high speed until there is no obvious solid or liquid stratification;
[0141] S3. Add thixotropic agent and multifunctional additive while stirring and cooling until the mixture becomes emulsion-like. Stop heating and stirring, cool the mixture to room temperature to obtain solder paste.
[0142] The performance of the solder paste composed of the flux paste and solder prepared in Comparative Example 1 and Comparative Example 2 was tested by the same method as in Example 1, and compared with Example 1. The results are shown in Table 13.
[0143] Table 13
[0144]
[0145]
[0146] It can be seen from the data in Table 13 that, compared with conventional high-temperature emulsification or high-temperature synthesis processes, the preparation method of the present invention has increased anti-collapse and spreading coefficient of the solder paste and reduced void rate, that is, the performance is more excellent.
[0147] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A soldering paste for improving the soldering quality of Mini LED, characterized in that: The solder paste comprises liquid resin, surfactant and multifunctional additive; According to the weight ratio, liquid resin: surfactant: multifunctional additive = 1: 0.1 ~ 0.5: 0.1 ~ 0.5; The liquid resin includes epoxy resin and polyurethane resin; according to the weight ratio, epoxy resin: polyurethane resin = 5 to 20:1; The surfactant is a blend of polyvinyl pyrrolidone and a liquid polymer alcohol compound; The multifunctional auxiliary agent is carboxylated PAMAM or a mixture of carboxylated PAMAM and dendritic PAMAM.
2. The soldering paste for improving the Mini LED soldering quality according to claim 1, characterized in that: The soldering paste further comprises a thixotropic agent, and the thixotropic agent is selected from at least one of hydrogenated castor oil, polyamide wax, and fumed silica.
3. The soldering paste for improving the Mini LED soldering quality according to claim 2, characterized in that: The amount of the thixotropic agent used is 0.5wt% to 10wt% of the liquid resin.
4. The soldering paste for improving Mini LED soldering quality according to claim 1, characterized in that: The liquid polymer alcohol compound is selected from at least one of polyethylene glycol, methoxy polyethylene glycol, polypropylene glycol and polyvinyl alcohol.
5. The soldering paste for improving the Mini LED soldering quality according to claim 1 or 4, characterized in that: In the surfactant, the weight ratio of polyvinyl pyrrolidone to the liquid polymer alcohol compound is 1:2 to 2:
1.
6. The soldering paste for improving Mini LED soldering quality according to claim 1, characterized in that: The number of generations of carboxylated PAMAM or dendritic PAMAM is 1 to 5.
7. The soldering paste for improving the Mini LED soldering quality according to claim 1 or 6, characterized in that: In the mixture of the carboxylated PAMAM and the dendritic PAMAM, the weight ratio of carboxylated PAMAM to dendritic PAMAM is 1 to 5:
1.
8. The method for preparing a soldering paste for improving the Mini LED welding quality according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: Mix epoxy resin, polyurethane resin and part of surfactant in proportion, heat to 50℃~70℃ and stir evenly; Add the multifunctional additive and the remaining surfactant simultaneously or step by step, and stir evenly at 80℃~120℃; Stop heating and continue stirring until the temperature drops to 50°C to 70°C. Stop stirring and cool to room temperature.
9. The method for preparing a solder paste for improving Mini LED welding quality according to claim 8, characterized in that: The preparation method comprises the following steps: Mix epoxy resin, polyurethane resin and part of surfactant in proportion, heat to 50℃~70℃ and stir evenly; Add thixotropic agent and stir until there are no particles or stratification; Add the multifunctional additive and the remaining surfactant simultaneously or step by step, heat to 80℃~120℃, and stir evenly; Stop heating and continue stirring until the temperature drops to 50°C to 70°C. Stop stirring and cool to room temperature.
10. The method for preparing a solder paste for improving Mini LED welding quality according to claim 8 or 9, characterized in that: The part of the surfactant refers to the amount used in this step which is 30wt% to 50wt% of the total amount of the surfactant.
Citation Information
Patent Citations
Epoxy resin curing agent and preparation method and application thereof
CN110105546A
Epoxy glue for mini LED and preparation method thereof
CN114774049A
Soldering paste and preparation method thereof
CN117620520A
Aqueous binder composition
EP2093266A1
Preparation method of phosphorus-free dendrimers modified with hydrophobic groups and their applications
JP6796235B1